2019
DOI: 10.4322/2526-8910.ctoao2007
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation, face validity and reliability of the Model of Human Occupation Screening Tool to Brazilian Portuguese

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
5
0
3
Order By: Relevance
“…We believed that these findings had influence on Stage 3 (back translation), where there was identified minimum disagreement between the two translators. This trend of having less modifications on the back translation has been observed on cross-cultural adaptation of other instruments [1,3,8,9]. We also observed that the single version of back translation, when compared to the original version of FMA, was very similar, which could be a result of the work on Stages 2, 3, and 4.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We believed that these findings had influence on Stage 3 (back translation), where there was identified minimum disagreement between the two translators. This trend of having less modifications on the back translation has been observed on cross-cultural adaptation of other instruments [1,3,8,9]. We also observed that the single version of back translation, when compared to the original version of FMA, was very similar, which could be a result of the work on Stages 2, 3, and 4.…”
Section: Discussionsupporting
confidence: 77%
“…In occupational therapy, the use of assessments is essential for practice and research. Most of the tools available were previously developed in countries where English is the first language [1]. However, countries in which English is not the primary language usually use standardized instruments developed internationally.…”
Section: Introductionmentioning
confidence: 99%
“…The expert panel review and semi-structured interviews were therefore strengths of our study design. Other studies have used similar combinations of methods to evaluate the validity of translated assessment forms [ 34 , 35 ]. Suggestions for linguistic changes in the instrument were made in all steps of the process, which is expected when performing a translation and validation of an instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Nesta direção, o processo de adaptação transcultural desse instrumento está em andamento em estudo conduzido no Programa de Pós-Graduação em Terapia Ocupacional da Universidade Federal de São Carlos (UFSCar), o que, futuramente, propiciará o início de investigações que fomentarão o ensino e a formação de terapeutas ocupacionais no país. Tal projeto faz parte de uma iniciativa de um grupo de pesquisa intitulado "Estudos em terapia ocupacional e reabilitação física, tecnologia assistiva e funcionalidade", o qual concentra uma linha de pesquisa com a aplicação de modelos e adaptação transcultural de instrumentos sobre ocupação (Mendes, 2020;Cruz et al, 2019).…”
Section: Discussionunclassified